Implementation of Pancasila Education Values in Mediation in Court - Yusuf, Muhammad; Tanjung, Alfian; Piliang, Fenny Mustika (Holistic Science, 2024)
Pancasila as a guide to life for the Indonesian people contains values that are relevant to be implemented in the mediation process in court in order to reach an agreement to resolve disputes in a win-win solution. Data from the Supreme Court of the Republic of Indonesia for 2022 shows a decreasing trend in resolving cases through mediation, only 19.07% were successfully resolved, while 59.14% were unsuccessful and 20.21% could not be implemented. The success of mediation, which shows a downward trend, is associated with the Pancasila values implemented in mediation. It is interesting to examine how mediation can implement Pancasila values and what challenges are faced in implementing Pancasila values in mediation in court. This research uses a qualitative method with a library research approach, collecting and analyzing data from various written sources, such as books, journal articles, reports and official documents that are relevant to the research topic. The research results show that Pancasila values can be implemented in mediation in court which becomes a reference for disputing parties, mediators, legal representatives and judges, so that the mediation process is based on high ethics and morals, fair treatment, constructive dialogue to find common ground, as well as active participation of the parties so that the resulting solution reflects mutual agreement and benefit. Obstacles include social and cultural factors in society which give rise to various points of view about mediation, skepticism regarding failed mediation experiences, weak knowledge and understanding of Pancasila values.